Characterising the dairy value chain from an agroecological perspective in the peri-urban area of Bobo-Dioulasso, Burkina Faso’s ‘Agroecological Living Landscape’ focus area - Sib, Ollo; Vall, Eric; Corniaux, Christian; Sodré, Etienne; Souleyman, Sanogo (2023)
In this study, we suggest a methodology for determining, in a participatory way, stakeholders' space for initiatives in a given value chain and, more specifically, their space for agroecological initiatives. By characterising this space for initiatives, we aim to identify the main areas where action is needed to step up the pace of agroecological transition by influencing stakeholder behaviour. This paper sets out four specific targets: 1) Introducing the concept of 'space for agroecological initiatives' 2) Providing a methodology for characterising and measuring such space 3) Clarifying the purpose of such characterisation and measurement 4) Illustrating the results of this methodology using Bobo Dioulasso's dairy value chain as a case study